Mungkinkah Menganggap Akhir Abad ke-20 Sastra Bali Memasuki Sebuah Era Keemasan? - I Nyoman Darma Putra (Pusat Kajian Bali Universitas Udayana, 2011)
AbstractIn the last two decades there have been pessimistic views on the futureof Balinese language and literature. These views hold that the youngBalinese generation is not interested in Balinese literature anymore and isreluctant to speak their mother tongue; hence the argument is that soonthis language and literature will be extinct. Close observation, however,shows that there is much evidence to indicate that toward the end ofthe twentieth century or early twenty first century the life of Balineseliterature has been lively, making it possible to argue that this literaturehas entered a new golden era. This article examines and discusses howvigorous Balinese literature has been by showing the lively literary readingand appreciation activities, the growing number of literary writing andpublication, and the emergence of literary appreciation through electronicmass media, especially ‘kidung interaktif’ programs on radio andtelevision stations. This study also discusses the contribution of Balineseliterature to the process of knowledge production and application ofsocial and critical theories.